PHONOLOGICAL CONCEPTS AND CONCEPT FORMATION: METATHEORY, THEORY AND APPLICATION - Fraser, Helen (International Journal of English Studies, 2009)
This paper presents an overview of Phenomenological Phonology (PP), including its metatheory, theory and application, for comparison with Cognitive Phonology (CP). While PP and CP are in close agreement at the theory level, there are some significant differences at the level of metatheory. PP considers phonological terms (such as phoneme and word) to be words like any others, and gives detailed consideration to the concepts behind such terms. It also considers pronunciation to be a form of behaviour, driven by concepts created through general concept formation processes. This has important consequences for practical application in the areas of pronunciation and literacy teaching.